Oxidative DNA damage is significantly correlated with flow-mediated dilation in patients with coronary artery disease - (:unkn) unknown (B C DECKER INC, 2008)
Background: Oxidative DNA damage was increased in patients with coronary artery disease (CAD) and correlated with the severity of the disease. Endothelial dysfunction plays a major role in atherosclerotic process. The aim of this study was to explore a relation between oxidative DNA damage and endothelial function in patients with CAD. Methods: Forty patients with CAD and 20 age- and sex-matched healthy controls were included. Endothelial function was assessed by brachial artery ultrasonography. The DNA damage was determined by cornet method. Results: The DNA damage scores after incubation with repair enzymes were found significantly higher in the patients with CAD (P = 0.04). There was a significant negative correlation between oxidized DNA damage scores and flow-mediated dilation (FMD) measures in the patients with CAD (r = -0.41; P = 0.009). Oxidized DNA damage scores were significantly and independently associated with FMD (standardized P = -0.455; P = 0.009) when adjusted by age, sex, smoking status, blood pressure, and cholesterol levels. Conclusions: The DNA damage scores were significantly inversely correlated with FMD measures. To our knowledge, this is the first study showing the presence of a relation between DNA damage scores and FMD.
Keywords: comet method; coronary artery disease; flow-mediated dilation; oxidative DNA damage; ENDOTHELIUM-DEPENDENT DILATION; HEALTHY-YOUNG ADULTS; ALKALINE COMET ASSAY; BRACHIAL-ARTERY; ATHEROSCLEROSIS; HYPERCHOLESTEROLEMIA; VASODILATION; VARIABILITY; DYSFUNCTION; DILATATION